PEMODELAN ANGKA HARAPAN HIDUP JAWA TIMUR (INDONESIA) MENGGUNAKAN REGRESI SEMIPARAMETRIK CAMPURAN SPLINE TRUNCATED DAN DERET FOURIER - Nisa', Khaerun; Budiantara, I Nyoman (MEDIA STATISTIKA, 2020)
Life expectancy is one of the indicators used to evaluate the governmentâ€™s performance in improving the well-being of the population. High life expectancy in an area indicates that people in the area have been assured of health and poverty has been well overcome, and vice versa. Based on national socioeconomic survey (SUSENAS) data, showing life expectancy in East Java Province from 2009 to 2013 increased by 69.15 years to 70,19 years. Although overall life expectancy in East Java province has increased, there are still some areas that have life expectancy below 65 years. This is not from the different characteristics of each religion. Therefore, the main purpose of this study is to model life expectancy in East Java using semiparametric regression with a mixed estimator of Spline Truncated and Fourier Series.Â  Based on the research that has been done, the results that modeling the data of life expectancy using mixed estimator of Spline Truncated and Fourier Series produced a value of R2 of 99,62% which means that the predictor variables are able to explain the response variabel life expectancy of 99.62%.